AADMM based shared energy storage planning for resilience improvement of renewable energy stations - Zhao, Long; Zhang, Jinping; Lv, Qingquan; Zhang, Zhenzhen; Gao, Pengfei; Zhang, Ruixiao (Frontiers in Energy Research, 2024)
The exponential proliferation of renewable energy has resulted in a significant mismatch between power supply and demand, especially during extreme events. This incongruity presents challenges in efficiently harnessing renewable energy and enhancing the resilience of the power grid. To address this issue, this paper proposes shared energy storage (SES) planning based on the adaptive alternating direction method of multipliers (AADMM). The objective is to fully leverage SES, enhance the local consumption level of renewable energy, ensure power grid resilience, and reduce operational costs. First, to ensure the effective utilization of SES while minimizing initial investment and construction costs, a planning model for SES is formulated. Secondly, to maximize the benefits for multiple prosumers within the renewable energy and SES station, a profit maximization model for multiple prosumers is established. Lastly, to guarantee the privacy security of SES and multi-prosumers while optimizing computational efficiency, a distributed computing model for SES based on AADMM is developed. The results of the example show that the proposed model can not only reduce the cost of 47.96 CNY, but also increase the power self-sufficiency rate by 21.86 %. In addition, compared with the traditional distributed optimization, the number of iterations of AADMM is increased by 47.05 %, and the computational efficiency is increased by 54.67 %.